Natural and technogenic components of megalopolis magnetic field - Orlyuk, M.; Romenets, A.; Orliuk, I. (Геофизический журнал, 2016)
Magnetic storm influence becomes more and more interesting for people. In this article we describe measurable magnetic field data from different megalopolis regions and from the underground passenger transport by the Kyiv city example. There were five observation points evenly situated among the city, and one metro route with direct and reverse direction movement. Collected information shows general situation with magnetic noise in populous cities. Smart- phones are very popular today so we have used one of them as a budget magnetometer in our research. Вплив магнітних бур на людину стає останнім часом все цікавішим. У статті викладено результати досліджень змінного магнітного поля техногенного походження в різних районах мегаполісу і підземному транспорті на прикладі м. Київ. Виміри проведені в п'яти пунктах у різних районах міста, а також у метро в обох напрямках руху поїзда. Отримана інформація показує загальну ситуацію з магнітним шумом у густонаселених містах. Як бюджетний варіант для вимірювань в метро використаний смартфон з вбудованим магнітометром.